ANALISIS TINGKAT PELAYANAN JALUR PEJALAN KAKI DI JALAN AHMAD YANI PONTIANAK - Anggia Dewi, Sapteriawuri; Widodo, Slamet; Nurhayati, Nurhayati (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
From 2020 to 2022, a pedestrian path has been built on Jalan Ahmad Yani, Pontianak City. The construction of this pedestrian path aims to provide public open space that is used for public purposes and is located in a space owned by the road. The pedestrian path separates pedestrians from private and public vehicles to guarantee safety and comfort. This study aimed to analyze the Level of Service (LOS) of sidewalks in Jalan Ahmad Yani Pontianak City. The method used, namely the survey method uses CCTV data at a predetermined point. The data used is in the form of sidewalk width, number of pedestrians, and pedestrian speed. Then the data is processed using the Transportation Research Board method and Sidewalk Planning Guidelines. The results showed that the value of space in Zone A, zone B, and Zone C was 18.40 m2/org, 12.25 m2/org, and 19.79 m2/org, then Zone A, zone B, and zone C were categorized as Level of Service (LOS) A.